A New Species of Wrigiitia R.Br. (Apocynaceae) from India - Bahadur, K. N.; Bennet, S. S. R. (Indian Forester, 1978)
A new species of Wrightia (Apocynaceae) viz. W. dolichocarpa Bhadur & Bennet sp. nov. is described from Nagarhaveli in Western India. It is allied to W.tinctoria R. Br. The latex from fruits is used by the cow-boys for making instant curd ia the field. It is a well-known plant in the area and is locally called dudh kudi.